Insight into ionic liquid as potential drilling mud additive for high temperature wells - Ofei, T.N. (Elsevier B.V., 2017)
Ionic liquids have been proposed as potential drilling mud additives that can maintain the rheological and filtration properties of water-based mud (WBM) at high temperatures. However, more insight is needed to understand the impact of ionic liquids on drilling mud which will enhance its application in drilling high temperature (HT) wells. This experimental study reports insights on the impact of 1-butyl-3-methylimidazolium chloride (BMIM-Cl) on the rheological and filtration behaviors of water-based drilling mud in the temperature range of 25 °C–200 °C and pressure of 1000 psi. The study was conducted by following the general drilling fluid testing methods and procedures recommended by the American Petroleum Institute (API). The results suggested that, the presence of BMIM-Cl significantly stabilized the mud viscosity, solid suspension capacity and filtration behaviors up to 180 °C as compared to the base mud (polymer water-based mud). The rheological property (τp/μp) values were found to decrease in the presence of BMIM-Cl at all studied temperatures. In addition, three commonly used fluid rheological models namely; Bingham plastic, Power law, and Herschel–Bulkley were employed to describe the rheology of polymer WBM with and without the addition of BMIM Cl for all temperatures. It was revealed that the rheological properties of the polymer WBM with and without BMIM-Cl were best described by the Herschel–Bulkley model with a shear-thinning behavior. The study has shown the applicability of BMIM-Cl as a potential drilling mud additive for stabilizing the drilling mud rheology and filtration control in HT wells. © 2017 Elsevier B.V.